2006
DOI: 10.1111/j.1365-313x.2006.02734.x
|View full text |Cite
|
Sign up to set email alerts
|

The N‐terminal ATPase AT‐hook‐containing region of the Arabidopsis chromatin‐remodeling protein SPLAYED is sufficient for biological activity

Abstract: SummaryThe SNF2-like chromatin-remodeling ATPase SPLAYED (SYD) was identified as a co-activator of floral homeotic gene expression in Arabidopsis. SYD is also required for meristem maintenance and regulates flowering under a non-inductive photoperiod. SNF2 ATPases are structurally and functionally conserved from yeast to humans. In addition to the conserved protein features, SYD has a large unique C-terminal domain. We show here that SYD is present as two forms in the nucleus, full-length and truncated, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 69 publications
2
41
0
2
Order By: Relevance
“…Thus, CLF and SYD/BRM have opposite effects at the regulatory regions of the common target genes AP3 and AG, with the dominant of the two activities ultimately determining the cell-fate choice. This idea is supported by the observation that a precocious increase in SYD activity, by premature removal of a negative regulatory domain, leads to upregulation of AG expression in leaves (48).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Thus, CLF and SYD/BRM have opposite effects at the regulatory regions of the common target genes AP3 and AG, with the dominant of the two activities ultimately determining the cell-fate choice. This idea is supported by the observation that a precocious increase in SYD activity, by premature removal of a negative regulatory domain, leads to upregulation of AG expression in leaves (48).…”
Section: Discussionsupporting
confidence: 60%
“…Coimmunoprecipitation was performed using nuclear extract prepared as described in ref. 48. ChIP experiments were performed as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Of the four potential Arabidopsis orthologues of the Snf2-type ATPase, only BRA-HMA (BRM) carries a bromodomain. In SPLAYED (SYD), the closest homologue of BRM, the bromodomain is replaced by a divergent C-terminal domain of unknown function (Su et al 2006;Jerzmanowski 2007;Kwon and Wagner 2007). The Arabidopsis genome encodes a single SNF5 orthologue, BUSHY (BSH, Brzeski et al 1999) and four diVerent (ATSWI3A, ATSWI3B, ATSWI3C and ATSWI3D) SWI3-type SWI/SNF core subunits (Sarnowski et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic analysis of the ATSWI3 gene family demonstrated that both ATSWI3A and ATSWI3B are essential for early embryonic development, whereas ATSWI3C and ATSWI3D aVect diVerent phases of vegetative and reproductive development (Sarnowski et al 2005). Functional studies of Snf2-type ATPases showed that the Arabidopsis syd mutant is viable and its phenotypic characteristics are clearly diVerent from those of atswi3c and atswi3d mutants (Wagner and Meyerowitz 2002;Su et al 2006). In contrast, phenotypic traits of brm and atswi3c insertion mutants are intriguingly similar (Sarnowski et al 2005;Hurtado et al 2006;Tang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…BRM is the most similar to its metazoan counterparts, while SYD shows a larger and acidic C-terminal domain of 200 kDa. This C-terminal domain is considered as autoinhibitory and is related to the control of the SYD protein accumulation (Su et al, 2006). Besides, MINU proteins are the shortest family members showing N-and C-terminal truncated domains.…”
Section: Swi/snf Chromatin Remodeling Complexes (Crc)mentioning
confidence: 99%